Elements of a Comparative Methodology in the Study of Religion - Freiberger, Oliver (Religions, 2018)
While comparison has been the subject of much theoretical debate in the study of religion, it has rarely been discussed in methodological terms. A large number of comparative studies have been produced in the course of the discipline's history, but the question of how comparison works as a method has rarely been addressed. This essay proposes, in the form of an outline, a methodological frame of comparison that addresses both the general configuration of a comparative studyits goal, mode, scale, and scopeand the comparative process, distinguishing operations of selection, description, juxtaposition, redescription, as well as rectification and theory formation. It argues that identifying and analyzing such elements of a comparative methodology helps, on the one hand, in evaluating existing comparative studies and, on the other, in producing new ones. While the article attempts to present the methodological frame in a concise form and thus offers limited illustrative material, the authors of the other essays in this collection discuss rich historical-empirical cases as they test the frame on their own comparative studies.